Strategi Perluasan Produksi Usahatani Cabai Rawit Di Kota Serang - Eha Eha; Sharifah Sharifah; Ardelia Nahdah Nurnudiya; Ragil Utami; Aliudin Aliudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Cayenne pepper is one of the horticultural commodities that has high and stable demand in the Indonesian market. However, the productivity of cayenne pepper at the farmer level is still relatively low due to limited land, suboptimal cultivation techniques, and lack of access to modern agricultural technology. This study aims to analyze strategies that can be applied to expand production and increase the productivity of cayenne pepper plants. The method used in this study is a qualitative descriptive method with a field study approach in several cayenne pepper production centers. Data collection techniques were carried out through observation, interviews with farmers, and literature studies. The results of the study showed that land expansion strategies through the utilization of idle land and intercropping systems, as well as the application of technologies such as the use of superior varieties, drip irrigation, and balanced fertilization can significantly increase crop yields.